Novel Antifungal Compounds, Spermine-Like and Short Cyclic Polylactates, Produced by Lactobacillus harbinensis K.V9.3.1Np in Yogurt - Mosbah, Amor; Delavenne, Emilie; Souissi, Yasmine; Mahjoubi, Mouna; Jéhan, Philippe; Le Yondre, Nicolas; Cherif, Ameur; Bondon, Arnaud; Mounier, Jérôme; Baudy-Floc’h, Michèle; Le Blay, Gwenaelle (Frontiers in Microbiology, 2018)
Lactobacillus harbinensis K.V9.3.1Np was described as endowed with high antifungal activity. Most of the studies associated this activity to the produced organic acids, i.e. lactic acid, acetic acid and hexanoic acid. The aim of this study was to purify and identify, other not yet described, antifungal molecules produced by L. harbinensis K.V9.3.1Np. when used in yogurt fermentation. Active compounds were extracted through several extraction processes using organic solvents and protein precipitation. The fractions of interest were purified using flash chromatography and preparative HPLC for specific characterization. The bioactive compounds identification was performed using Nuclear Magnetic Resonance and Mass Spectrometry. Activity tests against Penicillium expansum and Yarrowia lipolytica showed that the active compounds from L. harbinensis K.V9.3.1Np. are the benzoic acid and a polyamine identified as a spermine analogue, which has not been reported earlier. However, the highest activity was shown by a mixture of short (n=2 to n=5) polycyclic lactates. Our overall results demonstrate the efficiency of the proposed extraction/purification approach. The new compounds described here have promising antifungal activities but further studies are still needed to decipher their mode of action and production pathways. Even though, they present an interesting potential application in food, feed, as well as, in pharmaceutical industries and could serve as alternative to chemical additives.